El bien común como idea política. John Stuart Mill, los liberales y sus críticos - Sanmartín, José (Foro Interno, 2006)
This essay is focused on the study of the common good idea in the ideological world of so-called classical liberalism. As a political idea, the search for a common good became a theoretical battleground where many strong empirical forces clashed with one another. The moral obligation that John Stuart Mill —and other Liberal thinkers of his times— postulated in order to fight against poverty, providing effective social contents for a truly democratic political agenda, was subsequently reduced by the next generation of Liberals. For them, to help —and even to be helped— was a matter of personal choice. With few exceptions, Liberalism gradually lost this rich tradition of politics as a moral duty.